Creation of a distributed energy system for the production of thermal and electric energy - Rustamov, Nassim; Berkimbayev, Kamalbek; Abdikulova, Zagipa; Meirbekova, Oxana; Issabekov, Zhanibek; Babakhan, Shokhrukh; Rakhmetova, Perizat (Eastern-European Journal of Enterprise Technologies, 2024)
The object of the study is the distributed generation (DG) system for remote areas where extending power lines is challenging or impossible. The study demonstrates how integrating electrical and thermal energy modules based on renewable energy sources (RES) into a common DG bus can ensure continuous energy supply. This approach provides both heat and electricity to consumers, independent of weather conditions an advantage over traditional systems reliant on variable sources like wind and solar energy. Numerical assessments suggest that the proposed system can improve local renewable resource utilization by approximately 20–30 % compared to single-source renewable setups. This enhanced efficiency results in a more stable power output, with fewer interruptions caused by low wind speeds or reduced solar irradiance. Economically, reducing dependence on diesel generators by about 15–25 % can translate into substantial fuel cost savings. In addition, shifting energy production away from non-renewable sources may cut greenhouse gas emissions by an estimated 10–20 %, contributing to environmental protection targets. In this research received lies in its solution for off-grid energy delivery in rural areas, which generally rely on expensive and frequently unreliable centralized energy infrastructure. By leveraging renewable energy sources and implementing a cogenerative DG system, the study significantly reduces reliance on traditional energy grids and enhances energy independence for remote facilities. The research highlights the practical value of the proposed solution, particularly for rural areas far from power lines and with limited access to traditional electricity systems. The suggested system not only provides continuous energy, but it also coincides with worldwide trends toward sustainable and decentralized energy solutions